Chimeric RNA isoforms generated by diverse mechanisms from two C-type lectins modulate innate immunity in arthropods - Ying Huang; Xin Huang; Li-Hua Zhang; Qian Ren (Proceedings of the National Academy of Sciences, 2025)
Chimeric RNA formation represents a critical mechanism for expanding protein functional diversity, yet its role in invertebrate immune adaptation remains poorly characterized. Here, we report that two C-type lectin genes ( MnLec2 and MnLec3 ) from distinct genomic loci in the oriental river prawn Macrobrachium nipponense undergo positionally flexible chimeric RNA formation via alternative trans-splicing and transcriptional slippage, generating 11 structurally diverse chimeric isoforms ( MnLec1 , MnLec4–13 ) with bidirectional exon joining. Crucially, pathogen challenges reprogram chimeric RNA frequencies to shift immune equilibrium, universally suppressing detrimental MnLec9 while promoting protective MnLec7 formation. Functional dissection confirms dual-action pathogen suppression, recombinant MnLec7 (rMnLec7) suppresses white spot syndrome virus replication by upregulating antimicrobial peptides and RNAi effectors, while accelerating Vibrio parahaemolyticus clearance and improving survival. Conversely, suppression of MnLec9 removes its immunosuppressive activity, synergistically enhancing host defense. This coordinated isoform rebalancing enables effective pathogen clearance. Thus, positional flexibility in chimeric RNA formation generates antagonistic isoforms that maintain immune homeostasis and deploy targeted defense upon infection, revealing an adaptive transcriptional strategy in arthropods.